Health risk assessment of PM10 exposure among Malaysian adult population based on physical activity pattern - Norlen Mohamed; Lokman Hakim S; Thahirahtul Asma Zakaria; Anis Salwa Kamarudin; Ahmad Riadz Mazeli; Sirajuddin Hashim (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Introduction Most health advisories related to outdoor physical activity during haze are general in nature. The advisories normally advise everyone to reduce or limit prolonged exertion or heavy exertion without mentioning the acceptable duration for performing outdoor physical activity causing difficulty for public to decide to stop or cancel a particular outdoor or sport event. The aim of this paper is to determine the acceptable duration for performing outdoor physical activity pattern based on API level. Methods Health risk assessment approach that comprises of hazard identification, exposure assessment, dose-response, and risk characterization steps were used to determine the potential inhaled dose and risk associated with performing the physical activity during haze. We have considered many factors that include time spent for physical activity patterns for Malaysian adult, age, physical intensity-specific inhalation rate (m3/min), and the indoor/outdoor ratio of PM10. A hypothetical exposure scenario of PM10 was created using the breakpoints of PM10 concentration for the calculation of respective API levels. Results The association between physical activity pattern, API level and risk quotient were presented in the form of risk radar diagram. In general, based on the average estimate, everyone should avoid high intensity physical activity and moderate exertion when API reach > 175 and > 200 respectively. Whereas, based on the high estimate, everyone should avoid high intensity physical activity and moderate exertion when API reach > 135 and > 150 respectively. Below the said API, the duration for performing prolonged exertion and heavy exertion should be adjusted according to the API level as stated in the recommended maximum duration for performing physical activity. Conclusions Reducing the physical activity is an effective strategy to lower the dose of inhaled pollutants and reduce the health risk during poor air quality. Based on the assessment, the recommended maximum duration for performing the physical activity based on API level was established as a guide for the authority or public to plan their activity during poor air quality.